Glimpses of library and information science - Isaac, K A (New Delhi Ess Ess, 2001)
These essays represent the views on various topics in Library and Information Science that deal with live issues and problems that arises in practical librarianship An insight into them will facilitate well informed approach to practising librarians. The
Keywords: Library sceince-Essays; Information science-Essays; Collection development (Libraries)-India; Classification-Books